Higher fasting plasma glucose levels within the normoglycaemic range and rotator cuff tears. Issue 4 (23rd September 2008) - Longo, U G; Franceschi, F; Ruzzini, L; Spiezia, F; Maffulli, N; Denaro, V
Abstract : Objective: To determine the plasma glucose levels in non-diabetic patients with rotator cuff tear. Design: Frequency-matched case–control study. Setting: University Teaching Hospital. Participants: The study included 194 subjects who were operated on at our institution. Group 1 included 97 consecutive patients (36 men and 61 women; mean age: 62.9 years, range 37 to 82) who underwent arthroscopic repair of a rotator cuff tear in 2007 and 2008. Group 2 (control group) included 97 patients (36 men and 61 women; mean age: 61.6 years, range 36 to 80) who underwent arthroscopic meniscectomy for a meniscal tear in the same period, and had no evidence of shoulder pathology. These patients were frequency-matched by age (within 3 years) and gender with patients of Group 1. Main outcome measure: Measurement of fasting plasma glucose levels. Results: Patients with rotator cuff tears (Group 1) showed statistically significantly higher fasting plasma glucose levels within the normoglycaemic range (p = 0.007) than patients with meniscal tear (Group 2). Conclusions: The present study suggests that normal, but in the high range of normal, increasing plasma glucose levels may be a risk factor for rotator cuff tear. An enhanced understanding of these factors holds the promise of new approaches to the prevention and management of rotator cuff tears.